A model to assess cloud enterprise resource planning adoption in small and medium-sized enterprises : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Information Systems, School of Mathematical and Computational Sciences, Massey University, Auckland, New Zealand. EMBARGOED until 31 July 2027. - Tongsuksai, Sunchai (Massey University, 2025)
In the current digital era, cloud enterprise resource planning (ERP) systems have evolved taking precedence over the on-premise ERP due to the convenience of software deployment and operation managed by third parties or cloud service providers (CSPs). This is specifically helpful to small and medium enterprises (SMEs), who usually are limited in resources. The cloud ERP is an innovative technology, and its application can play a crucial role for SMEs to compete in the global market. There is a lack of research that looks at the benefits, characteristics, critical success factors (CSFs), and challenges of cloud ERP adoption in SMEs, specifically in the New Zealand (NZ) context. Thus, the objectives of this study are (1) to identify the benefits of adopting cloud ERP systems in New Zealand SMEs, (2) to examine the influential characteristics for the adoption decision of these systems, and (3) to evaluate the CSFs and the challenges that impact their adoption in SMEs. This study develops and uses a conceptual model, which combines technology, organisation, and environment (TOE) and unified theory of acceptance and use of technology (UTAUT) frameworks, to examine the influential characteristics of the technological, organisational, environmental and individual dimensions for cloud ERP adoption in NZ SMEs. A qualitative research design is deployed which is conducted in two phases in this study. In the initial preliminary study phase, semi-structured interviews are conducted with ERP vendors, who are experts and critical players in cloud ERP deployment, to gather in-depth knowledge on the current practices of cloud ERP adoption in NZ SMEs. In the second main study phase, two SMEs from NZ are interviewed to collect data from practitioners and company managers who are involved in the adoption of cloud ERP in their companies. The data collected from these case studies are evaluated through cross-case analyses and compared with the preliminary study findings and extant literature to arrive at the study results. A revised and extended empirical model is developed based on the study findings. The findings of this study highlight the benefits of adopting cloud ERP systems in New Zealand SMEs. The key benefits include cost reduction, system and data accessibility, scalability, and effortless integration with other applications. This study further highlights the characteristics that influence cloud ERP adoption decisions in NZ SMEs, as well as identifies novel characteristics that affect this adoption decision, such as system quality (technological dimension), organisational culture (organisational dimension), government funding support (environmental dimension) and personal innovation (individual dimension). Furthermore, the CSFs and challenges associated with adopting cloud ERP systems in NZ SMEs are discussed. The key CSFs include education and training for users, having knowledge of cloud ERP, and clear understanding requirements of cloud ERP adoption. The key challenges include lack of awareness and knowledge, incorrect migration process, and ineffective project management. These insights enhance the understanding of academics and practitioners regarding the benefits, characteristics, CSFs, and challenges of adopting these systems in SMEs.
Embargoed until 31 July 2027
Keywords: cloud ERP systems, SMEs, IS adoption theories; Cloud computing; Enterprise resource planning; Small business; Technological innovations; New Zealand; 460601 Cloud computing